Oman : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report on Oman's Observance of Standards and Codes examines Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. Omani authorities have strongly committed to adhering to internationally accepted standards and good practices in statistics. The authorities have taken several important measures such as implementing the latest international statistical standards and/or moving in that direction, and participating in the General Data Dissemination System (GDDS) and regularly updating the GDDS metadata.